DNA methylation site loss for plasticity-led novel trait genetic fixation - Takafumi Katsumura; Suguru Sato; Kana Yamashita; Shoji Oda; Takashi Gakuhari; Shodai Tanaka; Kazuko Fujitani; Toshiyuki Nishimaki; Tadashi Imai; Yasutoshi Yoshiura; Hirohiko Takeshima; Yasuyuki Hashiguchi; et al. (Proceedings of the National Academy of Sciences, 2026)
Phenotypic plasticity allows organisms to adapt traits in response to environmental changes, yet the molecular basis by which such plastic traits become genetically fixed remains unclear. Here, we investigated gut-length plasticity in medaka fish ( Oryzias latipes ) through genome-wide methylation profiling, CRISPR/Cas9-mediated deletion, and population genomic analyses. We found that seasonal methylation of CpG sites upstream of the Plxnb3 is correlated with gut-length plasticity, and deletion of this region abolishes plasticity. Additionally, standing variation in Ppp3r1 is associated with genetically fixed longer gut length in populations lacking plasticity. These results suggest that loss of epigenetic regulation via CpG site reduction triggers the genetic fixation of novel traits. Our findings provide molecular evidence linking epigenetic plasticity and genetic assimilation, advancing understanding of plasticity-led evolution in natural populations.